Optimalisasi Penggunaan Bahasa Iklan Interaktif dalam Pembuatan Iklan Online Produk Unggulan di Kelurahan Semarapura Kaja - Ni Putu Sri Mariyatni; Agus Darma Yoga Pratama; I Gusti Ayu Agung Dian Susanthi (Linguistic Community Services Journal, 2021)
Klungkung Regency is not only famous for producing songket and endek fabrics, but there are still many other Micro, Small, Medium Enterprises (MSMEs) that have been born and developed there. Semarapura Kaja Village is one of the MSME centers which certainly has a lot of potential that must be supported and developed so that it can become bigger and more independent. However, not all of these MSMEs have adequate capital, strategies, and support to be able to develop rapidly so that synergy and collaboration with the government and other parties are needed to overcome these problems. One solution that can be offered is to carry out promotional activities with interactive advertising language to attract consumer interest through online media in the hope of expanding market share and of course increasing income for MSME in Semarapura Kaja Village. This Community Partnership Program (PKM) educates and assists MSME to create good promotion and marketing strategies, either through print or online media. Assistance in optimizing the use of interactive advertising language in making online advertisements for superior products in Semarapura Kaja Village is targeting MSME who sell Balinese traditional clothing as one of the characteristics of Klungkung Regency which is the center of MSME traditional clothing. In its implementation, it was found that people are still very ignorant not only about advertising language but also with how to create, manage, and develop social media for promotion because there are still social media such as: Instagram and Facebook that are not effective and even not active in uploading content so that the form of implementation of assistance is direct and not in groups to maximize the results. MSMEs that are partners in the Community Partnership Program (PKM) are Dex's Pong and Tri Arta Collection. MSME have been assisted to socialize the importance of professionally managed social media with interactive advertising language, how to create attractive visual content for potential customers, to the importance of publication in print or online media. It is hoped that MSME will be able to consciously and independently promote their products in the future through the media consistently and continuously.